Report on “13th Arab Congress of Plant Protection”, Hammamet, Tunisia, 16-21 October 2022 - Kumari, Safaa (The Arab Society for Plant Protection, 2022)
13th Arab Congress of Plant Protection (13th ACPP), organized by the Arab Society of Plant Protection (ASPP) in collaboration with the Ministry of Agriculture, Water Resources and Fisheries of Tunisia, represented by the National Institute of Agronomic Research of Tunisia (INRAT), held during the period 16-21 October 2022 in Hammamet, Tunisia. A total of 270 scientists and graduate students from Egypt, Jordan, Sudan, Syria, Lebanon, Morocco, Algeria, Tunisia, Libya, Oman, UAE, Palestine, Mauritania and Saudi Arabia participated in this event. In addition, experts from outside the region, USA, United Kingdom, Italy, France, Switzerland, Turkey, Germany, Kenya and Pakistan, also participated in this congress. In addition, scientists from the International Organizations such as FAO, CIMMYT, ICARDA, CIHEAM, EPPO, MPU, ACSAD, AOAD, and IOFS attended the congress. ICARDA was one of the Gold sponsors, and CGIAR Germplasm Health Units (GHUs) was one of the Bronze sponsors of the 13th ACPP. Safaa Kumari (Head of ICARDA’s Seed Health Lab/Plant Virologist) was the senior editor of the abstracts book of 13th ACPP and authors/co-authors in 5 abstracts (https://hdl.handle.net/10568/127320). In addition, Safaa Kumari was elected as a President of the Arab Society for Plant Protection for the period 2023-2025. Mr Abd-Al Rahman Moukahel (Senior Research Assistant, Seed Health Lab - Lebanon) was selected for the best oral presentation award present by graduate students.